Enrichment of Doogh with Olive Leaf Extract and Investigation of Its Physicochemical, Microbial, and Sensory Properties during Storage at Room Temperature and Refrigerator - Laya Kalavari; Negin Nasiri; Fatemeh Ahmadian; Hamed Kioumarsi (Journal of Multidisciplinary Applied Natural Science, 2023)
Doogh is a popular Iranian drink with high nutritional value and in recent years has attracted the attention of many consumers. Nowadays, the problems caused by malnutrition and lack of useful compounds with high nutritional value and increasing shelf life are essential in the food industry. This research was performed in Shirin Cheshmeh Dairy Production Company and all experiments were performed in the Food Control Laboratory of the Food and Drug Administration, Guilan University of Medical Sciences. In this study, olive leaf extract was added to doogh at five levels of zero, 0.2, 0.5, 1, and 2% and stored for 45 days, its physicochemical, microbial, and sensory properties at two refrigerators at 2°C and room temperature 25 ° C were evaluated. Sampling was analyzed on days 0, 15, 30, and 45 days in 3 replications with Duncan's statistical analysis. The effect of using different treatments and storage time on most characteristics showed a significant difference. This study showed that the effect of olive leaf extract on the pH, mold, and yeast of the treatments is decreasing and the percentage of acidity and serum volume is increasing. According to the hedonic method, the acceptability of treatment 2 on the 15th day of maintenance was higher. In general, according to the results, it can be said that the production of useful products with plant compounds can promote an effective step to produce and design useful drinks in the consumer market and food industry factories.